Integrating Indragiri Hulu Local Wisdom into Audiovisual Math Module for Elementary Education - Yusmia Rika Subekti; Herlinawati Herlinawati; Yogi Yunefri (STAI Hubbulwathan Duri, 2024)
This study aimed to evaluate the effect of local wisdom-based audiovisual modules on improving learning outcomes in mathematics among second-grade students at YMI Tani Makmur Elementary School. The research employed a purposive sampling method to select students studying two- and three-dimensional shapes, aligning with the developed module. The study involved designing the module, validating it through expert reviews, and assessing student responses. Validation was conducted by teaching material experts (focusing on content and evaluation) and media experts (focusing on design, interactivity, and communicativeness). Expert validation results indicated an average score of 72.3% from material experts, categorized as